A Simple Rectification Method of Stereo Image Pairs with Calibrated Cameras - Huihuang Su; Bingwei He (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
To improve the efficiency of matching the corresponding points, stereo rectification is used to make the corresponding epipolar lines of image pairs be placed in the same horizontal lines or vertical lines in stereovision. In order to avoid the complicated calculation of many previous algorithms such as based on epipolar lines, based on fundamental matrix or directly depend on corresponding points, a simple and convenient rectification method of stereo image pairs with calibrated cameras is proposed in this paper. The method firstly establishes two virtual cameras with parallel optical axis by coordinate system transformation based on the pose relationship of the two cameras from calibration results. Secondly, it re-projects the points of the original image onto image planes of the virtual cameras through geometrical method, and then realized the stereo rectification. The experiments of real stereo image pairs show that the proposed method is able to realize the rectification of stereo image pairs accurately and efficiently.